MIGRATIONS AND MIGRANTS IN THE PRESS MEDIA IN CHILE: THE DELICATE RELATIONSHIP BETWEEN CONTROL POLICIES AND RACIALIZATION PROCESSES - Stefoni, Carolina; Brito, Sebastian (Revista de Historia Social y de las Mentalidades, 2019)
This article analyzes the overlapping of the political discourse of the current government of President Piñera (2018-2022) and the discourse of the media regarding migration and migrants. The article states that in both speeches there is a close relationship between the way of representing migrants (racialized and stereotyped) and the control policies that have been followed through measures implemented in the current administration. For this we developed three central ideas: the media have been a space hegemonized by the Ministry of Interior; the media reproduce the idea of †‹†‹migration as a problem and reinforce certain stereotypes associated with Haitian migration (poor, marginal, vulnerable) and Venezuelan (crisis, emergency, overflow) and finally the government has been effective in installing the ideology ” to order the house ”that acts as a dominant metaphor that encloses an ideological position, reducing reality to a simple idea with high manipulative power. 197 news items appeared in the media between April 2018 and August 2019 in press media available online.